Reading as dialogical document work: possibilities for Library and Information Science - Lundh, Anna Hampson; Dolatkhah, M. (Emerald Group Publishing Limited, 2016)
Purpose – The purpose of this paper is to introduce a dialogically based theory of documentary practices and document work as a promising framework for studying activities that are often conceptualised as information behaviour or information practices within Library and Information Science (LIS). Design/methodology/approach – An empirical example – a lesson on how to read railway timetables – is presented. The lesson stems from a research project including 223 Swedish lessons recorded in Swedish primary schools 1967-1969. It is argued that this lesson, as many empirical situations within LIS research, can fruitfully be regarded as documentary practices which include document work such as reading, rather than instances of information behaviour. Findings – It is found that the theoretical perspective of dialogism could contribute to the theory development within LIS, and function as a bridge between different subfields such as reading studies and documentary practices. Research limitations/implications – The framework is yet to be applied on a larger scale. This would require a willingness to go beyond the entrenched idea of information as the core theoretical concept and empirical object of study within LIS. Social implications – The theoretical framework offers a view of the relations between individuals, documents, and social contexts, through which it is possible to explore the social significance of core LIS concerns such as reading, literacy, and document work. Originality/value – The theoretical framework offers an alternative to the monologist, information-based theories and models of people’s behaviours and practices prevalent in LIS.